The Impact of Sugar Intake, Household Income, and Maternal Education on the Occurrence of Dental Caries in Children: A Meta-Analysis - Arddha Maha Pawitra Dwi Puspita Dewi; Eti Poncorini Pamungkasari; Bhisma Murti (Journal of Epidemiology and Public Health, 2024)
Background: In Indonesia, the prevalence of dental caries in early childhood is still very high, around 93%. This study aims to analyze and estimate the magnitude of the relationship between sugar consumption, family income, and maternal education and the incidence of dental caries in children, through a meta-analysis of primary studies conducted by previous authors. Subjects and Method: This study is a systematic review and meta-analysis using PICO as follows, Population: children aged 1 to 5 years 11 months, Intervention: high sugar consumption, high family income, high maternal education, Comparison: low sugar consumption, low family income, low maternal education, and Outcome: dental caries. The articles used in this study were obtained from three databases, namely PubMed, Google Scholar, and Science Direct, using the keywords "Sugar" OR "Sweet food" AND "Household income" OR "Parental income" AND "Parental education" OR "Education status" AND "Dental caries" AND "Child" OR "Children" AND "Cross-sectional" AND “aOR”. The included articles were full-text in English, with a cross-sectional study design from 2013 to 2023, and reported adjusted Odds Ratio (aOR) in multivariate analysis. Article selection was carried out using the PRISMA diagram and analyzed using the ReMan 5.3 application. Results: A total of 11 cross-sectional were selected for meta-analysis. Children who frequently consume sugar have an increased risk of dental caries 1.50 times compared to children who rarely consume sugar, and this is statistically significant (aOR=1.50; 95% CI=1.32 to 1.70; p<0.001). Children from families with high incomes had a reduced risk of dental caries 0.65 times compared to children from families with low incomes, and this was statistically significant (aOR=0.65; 95% CI=0.59 to 0.71; p<0.001). Children who have highly educated mothers have a reduced risk of dental caries 0.71 times compared to children who have mothers with low education, and this is statistically significant (aOR=0.71; 95% CI=0.64 to 0.78; p<0.001). Conclusion: Sugar consumption statistically significantly increases the incidence of dental caries in children. High family income and high maternal education statistically significantly reduce the incidence of dental caries in children.